In vitro characterization of taurine transport using the human brain microvascular endothelial cell line as a human blood-brain barrier model - Tega, Yuma; Kawauchi, Yusuke; Akanuma, Shin-ichi; Inagaki, Mai; Tachikawa, Masanori; Hosoya, Ken-ichi (Drug metabolism and pharmacokinetics, 2025)
Taurine, a sulfur-containing β-amino acid, has various roles in the brain including cellular osmoregulation and neuroprotection. For adequate supply to the brain, taurine has to pass through the blood-brain barrier (BBB); however, the associated mechanism behind crossing the human BBB is not fully understood. Therefore, we characterized taurine transport in vitro using the human brain microvascular endothelial (hCMEC/D3) cell line, a model of human BBB function. [3H]Taurine uptake by hCMEC/D3 cells exhibited time-, as well as extracellular Na+- and Cl−-dependence. The uptake was saturable with a Km of 19 μM and was inhibited by GABA at an IC50 of 328 μM, which were similar to Km values of taurine transporter (TauT)-mediated transport of taurine and GABA, respectively, suggesting that TauT is a major contributor to taurine uptake. For distribution to the brain, taurine must undergo cellular efflux after uptake. Taurine efflux from hCMEC/D3 cells increased for at least 60 min, and monocarboxylate transporter 7 (MCT7)-targeted siRNA significantly reduced MCT7 mRNA levels and [3H]taurine efflux by 93 % and 12 %, respectively, suggesting that MCT7 partly contributes to taurine efflux from hCMEC/D3 cells. Taken together, these results suggest that TauT and MCT7 function cooperatively in the human BBB. [Display omitted]